Three-dimensional magnetic flux-closure domain patterns in MnAs thin films on GaAs(001) - Engel-Herbert, R; Hesjedal, T; Schaadt, D (2007)
The magnetic microstructure of single-crystalline MnAs films on GaAs(001) has been investigated. Magnetic force microscopy (MFM) reveals a three-dimensional magnetization pattern that is in disagreement with the simple domain picture observed by surface-sensitive magnetic imaging. Here, we present a consistent micromagnetic picture of MnAs thin films in the ferromagnetic stripe phase, which appears in the course of the phase transition. A number of equilibrium magnetization patterns of the stripes are found that are, in fact, based on flux-closure domain patterns in the basal plane of MnAs. The simulation of a stripe array yields excellent agreement with the measured surface magnetization. The experimentally observed stray field contrast was confirmed by MFM contrast simulations based on these equilibrium magnetization patterns. © 2007 American Institute of Physics.